2004
DOI: 10.1379/483.1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytoprotective proteins, heat shock protein 70and metallothioneins, in tissues ofOstrea edulis exposed to heat andheavy metals

Abstract: Heat shock proteins (Hsps) are constitutively expressed in cells and involved in protein folding, assembly, degradation, intracellular localization, etc, acting as molecular chaperones. However, their overexpression represents a ubiquitous molecular mechanism to cope with stress. Hsps are classified into families, and among them the Hsp70 family appears to be the most evolutionary preserved and distributed in animals. In this study, the expression of Hsp70 and the related messenger ribonucleic acid (mRNA) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 46 publications
4
75
1
12
Order By: Relevance
“…For example, the expression of HSP70 and HSP90 in oysters exposed to Cd showed a significant enhancement [14,37]. However, no significant difference of MgHSPA12A expression was observed when Cd concentration increased to 50 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of HSP70 and HSP90 in oysters exposed to Cd showed a significant enhancement [14,37]. However, no significant difference of MgHSPA12A expression was observed when Cd concentration increased to 50 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more recent evidence showed that HSPs are involved in the cell response to most environmental and physiological stressors (reviewed by Wegele et al 2004). This includes studies in molluscs (CruzRodriguez et al 2000;Snyder et al 2001;Boutet et al 2003;Piano et al 2004). Here again, semi-quantitative methods were used to obtain evidence for an increase in various stressing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…**P≤ 0.01 when compared to DMSO controls (n=6, ±SEM) Discussion Aquatic organisms exhibit altered HSP expression when exposed to range of stressful conditions including seasonal acclimatisation, climate change (increase and decrease in temperature), competition for space, food availability, wave exposure, heavy metal exposure and laboratory adaptation (Buckley et al 2001;Franzellitti and Fabbri 2005;Helmuth et al 2002;Helmuth and Hofmann 2001;Kefaloyianni et al 2005;Lund et al 2006;Todgham et al 2007;Tomanek and Sanford 2003). For molluscs, HSP-like molecules have been identified in the sea slug, Aplysia californica, the oysters, Crassostrea virginica, O. edulis, and Crassostrea gigas, the mussel, Mytilus galloprovincialis, and the clams Tapes philippinarum and Scapharca inaequivalvis (Kuhl et al 1992;Piano et al 2002Piano et al , 2004Tirard et al 1995). Furthermore, HSP70 genes have been cloned and characterised in the B. glabrata embryonic (Bge) cell line and in M. galloprovincialis (Kourtidis et al 2006a, b;Laursen et al 1997).…”
Section: Hsp70 Protein Reduction May Be Regulated By Effects Of Esps mentioning
confidence: 99%